EFISIENSI METODE DEEP FLOW TECHNIQUE UNTUK MENURUNKAN BOD, COD DAN TSS PADA LIMBAH CAIR DOMESTIK MENGGUNAKAN TUMBUHAN KAYU APU DAN KANGKUNG AIR - Raka Rulistyanto Prakoso Putra; Okik Hendriyanto Cahyonugroho (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
In Indonesia, there are various environmental pollutants, one of which comes from household activities. Therefore, various ideas emerged in dealing with the polluted environment. One of them is using the phytoremediation method. In this study using wood apu (pistia stratiotest l) and water spinach (ipomea aquatica) grown using a hydroponic system. In hydroponics, there are two systems, namely DFT (deep flow technique) and NFT (nutrient film technique). In this study, using two kinds of systems, with the addition of aeration and without aeration, with variations in the distance between plants of 5cm, 10cm and 15cm and using two types of plants, namely water spinach and apu wood. The length of the study was 15 days, the first 7 days of acclimatization and the last 8 days of the main study. The results showed that the most optimal treatment was found in apu wood plants with a distance between plants of 5cm, with the addition of aeration and using the DFT system to achieve BOD 58.41%, COD 32.36% and TSS 62%.